2022
DOI: 10.3390/cancers14143524
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Chemoresistance-Associated ABC Proteins in Hepatobiliary, Pancreatic and Gastrointestinal Cancers

Abstract: Hepatobiliary, pancreatic, and gastrointestinal cancers account for 36% of the ten million deaths caused by cancer worldwide every year. The two main reasons for this high mortality are their late diagnosis and their high refractoriness to pharmacological treatments, regardless of whether these are based on classical chemotherapeutic agents, targeted drugs, or newer immunomodulators. Mechanisms of chemoresistance (MOC) defining the multidrug resistance (MDR) phenotype of each tumor depend on the synergic funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 189 publications
(316 reference statements)
0
12
0
Order By: Relevance
“…Chemotherapy is a drug-based treatment to destroy cancer cells [ 17 , 19 ]. This treatment is used to reduce the tumor before surgery or to delay its growth until surgery [ 17 , 20 ]. Classical chemotherapeutic agents have their primary effect on macromolecular synthesis or function, contributing to cell death.…”
Section: Cancer Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemotherapy is a drug-based treatment to destroy cancer cells [ 17 , 19 ]. This treatment is used to reduce the tumor before surgery or to delay its growth until surgery [ 17 , 20 ]. Classical chemotherapeutic agents have their primary effect on macromolecular synthesis or function, contributing to cell death.…”
Section: Cancer Therapiesmentioning
confidence: 99%
“…Therefore, in selecting an effective drug, it is necessary to find an agent that has a marked inhibitory or growth-controlling effect on cancer cells and a minimal toxic effect on the host. Even so, there are several side effects in the body such as fatigue, nausea, loss of appetite and hair, and even blood clots [ 17 , 20 ]. Combination chemotherapy is a grouping of medications that is usually more effective in producing responses and prolonging life than medications used separately (monotherapy) and sequentially [ 17 ].…”
Section: Cancer Therapiesmentioning
confidence: 99%
“…Recent reports indicated that the high expression of MRP2 relates to chemoresistance in HCC patients resulting in low efficacy of HCC treatment. [39,40] Therefore, the current developed 3D-HepG2 coculture model may be useful for studying the mechanism of drug resistance and predicting efficacy of novel anticancer drugs for HCC treatment. The highest MRP2 expression in 3D-imHC mono and coculture models was observed at day 10 (Figure 4B).…”
Section: Protein Expression Of Liver-specific Biomarkersmentioning
confidence: 99%
“…Paclitaxel also potentiates gemcitabine efficacy by increasing intratumor uptake and inhibiting its inactivation by catabolizing enzymes [ 10 , 11 ]. Mechanisms underlying paclitaxel resistance in PDAC are poorly understood [ 12 , 13 ]. Three studies have investigated paclitaxel resistance in PDAC, reporting that it involves metabolic adaptation [ 14 ], sustained c-MYC activation [ 15 ], and expression of orexin receptor type 1 [ 16 ].…”
Section: Introductionmentioning
confidence: 99%